2015
DOI: 10.1182/blood-2015-02-630335
|View full text |Cite|
|
Sign up to set email alerts
|

Topical resiquimod can induce disease regression and enhance T-cell effector functions in cutaneous T-cell lymphoma

Abstract: Key Points Topical resiquimod is a safe, effective therapy for early-stage CTCL that can clear both treated and untreated skin lesions. Responding patients had T-cell recruitment into skin, enhanced T-cell effector functions, and eradication of the malignant T-cell clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(142 citation statements)
references
References 25 publications
2
130
0
10
Order By: Relevance
“…Consistent with this conclusion, administration of the Th1 cytokines IL-12 and IFN-γ can induce lesional regression associated with increased numbers of cytotoxic CD8 + T cells in the resolving skin, and treatment with Toll-like receptor (TLR) agonists that stimulate cellular immunity have shown clinical efficacy in CTCL patients [136–144]. For example, a recent clinical phase 1 trial reported that 75 % of the enrolled CTCL patients had significant improvement in skin lesions treated topically with resiquimod gel (TLR-7 and TLR-8 agonist) and 30 % had clearing of all treated lesions.…”
Section: Drugs That Stimulate Cellular Immunity Induce Disease Regresmentioning
confidence: 92%
“…Consistent with this conclusion, administration of the Th1 cytokines IL-12 and IFN-γ can induce lesional regression associated with increased numbers of cytotoxic CD8 + T cells in the resolving skin, and treatment with Toll-like receptor (TLR) agonists that stimulate cellular immunity have shown clinical efficacy in CTCL patients [136–144]. For example, a recent clinical phase 1 trial reported that 75 % of the enrolled CTCL patients had significant improvement in skin lesions treated topically with resiquimod gel (TLR-7 and TLR-8 agonist) and 30 % had clearing of all treated lesions.…”
Section: Drugs That Stimulate Cellular Immunity Induce Disease Regresmentioning
confidence: 92%
“…Dying tumor cells release intracellular components such as high-mobility-group box 1, ATP, and DNA, which are recognized, in turn, by receptors such as Toll-like receptor (TLR) 4 (Apetoh et al, 2007), P2X7 receptor (P2X7R) (Ghiringhelli et al, 2009), and stimulator of interferon genes (STING) (Deng et al, 2014) to regulate immune responses against tumors. Accordingly, a number of innate sensor agonists are being brought forward for investigation in cancer patients (Corrales and Gajewski, 2015; Kaczanowska et al, 2013; Rook et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, with this topical treatment, not only the treated but also the untreated lesions showed regression. Activation of DCs, enhanced CD8+ T-cell effector function, and a trend towards improved NK cell function were demonstrated but did not correlate with response [62]. Imiquimod is FDA-and EMA-approved for actinic keratosis, superficial basal-cell carcinoma, and condylomata accuminata [23,24].…”
Section: Toll-like Receptor Agonistsmentioning
confidence: 99%